Realizing Total Quality Management through Strategic Management Implementation in School - Syarifudin, Aip (JURNAL AL-TANZIM, 2023)
This research aims to analyze the implementation of strategic management to create quality Early Childhood Education (PAUD) institutions in realizing a good learning process and school culture. This research uses a qualitative approach with a case study type. Data collection techniques are carried out through interviews, observation, and documentation. The research results show that strategic management is critical to implement at the Al-Fatah PAUD institution so that it impacts improving the quality of education at the Al-Fatah PAUD institution. Strategies to improve the quality of education at Al-Fatah PAUD institutions can be carried out through 1) curriculum development, 2) human resource development, 3) adequate infrastructure, 4) improved student achievement, and 4) creating branding for the Al-Fatah PAUD institution. The implications of this research emphasize the need to increase synergy between maintenance and quality functions in organizations to meet the challenges of a highly competitive environment. This study highlights that significant achievements in performance can be achieved through synergistic and strategic implementation of TQM-TPM over a long period.